The effect of lubricant film on the dynamic response and signal transmission of moving load dynamic problems. (April 2021) - Liu, Shuo; Cui, Yi; Wang, Yi; Fu, Yan; Lv, Binglin; Qian, Yuehua
Highlights: A comprehensive model of moving load dynamic problems with lubricant film is established. A general numerical procedure of the mathematical model is given and verified. The dynamic response and the transmission law of load in the mechanism are studied in detail. The transfer rate of excitation signal through the system has multiple peaks in the frequency domain. Abstract: Moving load dynamic problems with lubricant film are common in engineering. Previous studies of this kind of problem often ignored lubricating oil film, or regarded oil film as a simple linear system. To avoid errors caused by the nonlinearity of oil film, hydrodynamic equations are used to describe the oil film subsystem accurately in this paper. By coupling the kinematic systems (moving mass and elastic carrying mechanism), a comprehensive model of moving load dynamic problems with lubricant film is established, and a general numerical procedure of the problem is given. Then the dynamic response and the transmission law of load in the mechanism are studied by taking a reciprocating friction pair of a typical marine engine as an example. Results show that the load transmission is not sensitive to low-frequency harmonic signals, but has a strong filterability to the mid-high frequency harmonic signals. It is also found that the transfer rate of excitation signal through the oil film does not decrease smoothly as frequency increases, and there exist multiple peaks in the frequency domain.